Skip to main content

Section 6.3 Linear Systems

Subsection 6.3.1 Qualitative Analysis

A first-order linear system of two differential equations with constant coefficients has the following form. I’ll stick to two equations for the majority of this section so that visualization is reasonable.
\begin{align*} x^\prime \amp = ax + by\\ y^\prime \amp = cx + dx \end{align*}
The nullclines of a linear system are the lines \(y = \frac{-a}{b} x\) and \(y = \frac{-c}{d}\text{.}\) The only steady state is \((0,0)\text{.}\) The six behaviours listed in the previous section (stable/unstable node, stable/unstable focus, saddle, centre) are all possible. However, for linear systems, these six cases are the only possible cases.

Subsection 6.3.2 Laplace Transforms for Linear Systems

One of the most reasonable way to solve linear systems of DEs with constant coefficients is through Laplace transforms. The Laplace transform will change the system of differential equations to a system of linear algebraic equations, which can be solved by any of the techniques for solving systems of linear equaiton (isolate and replace, add and subract equations, various matrix techniques from linear algebra, etc.) I’ll show how this works over a series of examples.

Example 6.3.1.

Here is the first example.
\begin{align*} x^\prime \amp = -y \\ y^\prime \amp = x \\ x(0) \amp = 0\\ y(0) \amp = 1 \end{align*}
I’ll take the Laplace transform, using the initial conditions given to me. Then I’ll solve the system of equations by isolating and replacing. After solving for both \(X\) and \(Y\text{,}\) I’ll reverse the transform to get the original functions back.
\begin{align*} sX \amp = -Y \implies X = \frac{-Y}{s} \\ sY -1 \amp = X \implies sY - 1 = \frac{-Y}{s} \\ sY + \frac{Y}{s} \amp = 1 \\ Y \amp = \frac{s}{s^2+1} \\ X \amp = \frac{-Y}{s} = \frac{-1}{s^2+1} \\ y \amp = \cos t \\ x \amp = - \sin t \end{align*}
In this case, the nullclines are simply the axes. The steady state \((0,0)\) is a centre. Figure 6.3.2 shows the nullclines and directions. Sine and cosine describe the coordinates of a circle, so the solutions match the qualitative analysis and this is, indeed, a centre.
Figure 6.3.2. First Linear System Example

Example 6.3.3.

Here is the second example.
\begin{align*} x^\prime \amp = 2x + 2y \\ y^\prime \amp = 2x - y \\ x(0) \amp = 1\\ y(0) \amp = 1 \end{align*}
I’ll take the Laplace transform, using the initial conditions given to me. Then I’ll solve the system of equations by isolating and replacing. After solving for both \(X\) and \(Y\text{,}\) I’ll reverse the transform to ge the original functions back. Partial fractions is needed to separate the rational functions that I get for both \(s\) domain functions.
\begin{align*} sX - 1 \amp = 2X + 2Y\\ sY - 1 \amp = 2X - Y \implies X = \frac{2Y+1}{s-2}\\ sY - 2 \left( \frac{2Y+1}{s-2} \right) + Y \amp = 1\\ (s+1) Y - \frac{4Y}{s-2} \amp = 1 + \frac{2}{s-2}\\ \left( \frac{s^2-s-6}{s-2} \right) Y \amp = 1 + \frac{2}{s-2}\\ Y \amp = \frac{s-2}{(s-3)(s+2)} + \frac{2}{(s-3)(s+2)} = \frac{s}{(s-3)(s+2)}\\ \amp = \frac{\frac{2}{5}}{s+2} + \frac{\frac{3}{5}}{s-3}\\ X \amp = \frac{2Y+1}{s-2} = \frac{2\left( \frac{s}{(s-3)(s+2)} \right) + 1}{s-2} = \frac{2s + s^2 - s - 6}{(s-3)(s-2)(s+2)}\\ \amp = \frac{(s+3)(s-2)}{(s-3)(s-2)(s+2)} = \frac{s+3}{(s-3)(s+2)} = \frac{\frac{6}{5}}{s-3} - \frac{\frac{1}{5}}{s+2}\\ x \amp = \frac{6}{5} e^{3t} - \frac{1}{5} e^{-2t}\\ y \amp = \frac{2}{5} e^{-2t} + \frac{3}{5} e^{3t} \end{align*}
In this case, the nullclines are \(y = -x\) and \(y = 2x\text{.}\) The steady state is a saddle point. The solutions are a mix of exponential growth and exponential decay; this mix of growth and decay fits the expected behaviour of a saddle point. Figure 6.3.4 shows the nullclines and directions.
Figure 6.3.4. Second Linear System Example

Example 6.3.5.

Here is the third example.
\begin{align*} x^\prime \amp = 2x + 3y \\ y^\prime \amp = 2x + y \\ x(0) \amp = 1\\ y(0) \amp = 1 \end{align*}
I’ll take the Laplace transform, using the initial conditions given to me. Then I’ll solve the system of equations by isolating and replacing. After solving for both \(X\) and \(Y\text{,}\) I’ll reverse the transform to ge the original functions back. Partial tractions is needed to separate the rational functions that I get for both \(s\) domain functions.
\begin{align*} sX - 1 \amp = 2X + 3Y\\ sY - 1 \amp = 2X + Y \implies X = \frac{3Y+1}{s-2}\\ sY - Y - 2 \left( \frac{3Y+1}{s-2} \right) \amp = 1\\ \left( \frac{s^2-3s-4}{s-2} \right) Y \amp = 1 + \frac{2}{s-2}\\ Y \amp = \frac{s-2}{(s-4)(s+1)} + \frac{2}{(s-4)(s+1)} = \frac{s}{(s-4)(s+1)} \\ \amp = \frac{\frac{4}{5}}{s-4} + \frac{\frac{-1}{5}}{s+1}\\ X \amp = \frac{3\frac{s}{(s-4)(s+1)} + 1}{s-2} = \frac{3s+s^2-3s-4}{(s+1)(s-4)(s-2)} \\ \amp = \frac{s^2-4}{(s+1)(s-4)(s-2)}\\ \amp = \frac{s+2}{(s+1)(s-4)} = \frac{\frac{6}{5}}{s-4} - \frac{\frac{1}{5}}{s+1}\\ x \amp = \frac{6}{5} e^{4t} - \frac{1}{5} e^{-t}\\ y \amp = \frac{4}{5} e^{4t} + \frac{1}{5} e^{-t} \end{align*}
In this case, the nullclines are \(y = \frac{-2}{3}x\) and \(y = -2x\text{.}\) The behaviour is again a saddle point and again there is a mix of positive and negative exponential terms. Figure 6.3.6 shows the nullclines and directions.
Figure 6.3.6. Third Linear System Example

Example 6.3.7.

Here is the fourth example.
\begin{align*} x^\prime \amp = 3x - 18y \\ y^\prime \amp = 2x - 9y \\ x(0) \amp = 1\\ y(0) \amp = 1 \end{align*}
I’ll take the Laplace transform, using the initial conditions given to me. Then I’ll solve the system of equations by isolating and replacing. After solving for both \(X\) and \(Y\text{,}\) I’ll reverse the transform to ge the original functions back. Partial tractions is needed to separate the rational functions that I get for both \(s\) domain functions.
\begin{align*} sX - 1 \amp = 3X - 18Y \\ sY - 1 \amp = 2X - 9Y \implies X = \frac{1-18Y}{s-3} \\ sY + 9Y - 2 \left( \frac{1-18Y}{s-3} \right) \amp = 1 \\ \left( \frac{s^2+6s+9}{s-3} \right) Y \amp = 1 + \frac{2}{s-3} \\ Y \amp = \frac{s-3}{(s+3)^2} + \frac{2}{(s+3)^2} = \frac{s-1}{(s+1)^2} \\ \amp = \frac{s}{(s+3)^2} - \frac{1}{(s+3)^2} = \frac{1}{s+3} - \frac{4}{(s+3)^2} \\ X \amp = \frac{1 - 19 \frac{s-1}{(s+3)^2}}{s-3} = \frac{s^2-12s+27}{(s-3)(s+3)^2} \frac{(s-9)(s-3)}{(s-3)(s+3)^2} \\ \amp = \frac{s}{(s+3)^2} - \frac{1}{(s-3)^2} = \frac{1}{s+3} - \frac{12}{(s+3)^2} \\ x \amp = e^{-3t} + 12 t e^{-3t} \\ y \amp = e^{-3t} + 4 t e^{-3t} \end{align*}
In this case, the nullclines are \(y = \frac{1}{6}x\) and \(y = \frac{2}{9}x\text{.}\) The steady state is a stable focus. The solutions are all decay terms, so they all tend to the steady state. This doesn’t really match the expected behaviour, which looks like rotation. This is an interesting example: the repeated factor leads to the \(t e^{-3t}\) terms, which do have more spinning motion that the general exponential terms. This is like the critically damped case for harmonic motion: it is very close to sinusoidal behaviour but not quite there. It would be very easy to interpret the trajectories as rotational; in this case, the qualitative analysis is misleading. Figure 6.3.8 shows the nullclines and directions.
Figure 6.3.8. Fourth Linear System Example

Example 6.3.9.

Here is the fifth example.
\begin{align*} x^\prime \amp = 6x - y \\ y^\prime \amp = 5x + 4y \\ x(0) \amp = 1\\ y(0) \amp = 1 \end{align*}
I’ll take the Laplace transform, using the initial conditions given to me. Then I’ll solve the system of equations by isolating and replacing. After solving for both \(X\) and \(Y\text{,}\) I’ll reverse the transform to ge the original functions back. Partial tractions is needed to separate the rational functions that I get for both \(s\) domain functions.
\begin{align*} sX - 1 \amp = 6X - Y \\ sY - 1 \amp = 5X + 4Y \implies X = \frac{1-Y}{s-6} \\ (s-4)Y - 5 \left( \frac{1-y}{s-6} \right) \amp = 1 \\ \left( \frac{s^2-10s+29}{s-6} \right) Y \amp = 1 - \frac{5}{s-6} = \frac{s-11}{s-6} \\ Y \amp = \frac{s-11}{s^2-10s_29} = \frac{s}{(s-5)^2+4} - \frac{11}{(s-5)^2 + 4} \\ \amp = \frac{s-5}{(s-5)^2+4} - \frac{6}{(s-5)^2 + 4} \\ X \amp = \frac{1 - \frac{s-11}{s^2+10s+29}}{s-6} = \frac{s^2-11s + 40}{(s-6)(s^2-10s+29)} \\ \amp = \frac{(s-6)(s-5)}{(s-6)(s^2-10s+19)} \\ \amp = \frac{s-5}{s^2-10s+29} = \frac{s-5}{(s-5)^2 +4} - \frac{1}{(s-5)^2 + 4} \\ x \amp = e^{5t} \cos 2t - 3 e^{5t} \sin 2t \\ y \amp = e^{5t} \cos 2t - \frac{1}{2} e^{5t} \sin 2t \end{align*}
In this case, the nullclines are \(y = 6x\) and \(y = \frac{-5}{4}x\text{.}\) The steady state is unstable node. The solutions have rotation in the sinusoidal terms and exponential growth, showing the outward spiral expected from an unstable node. Figure 6.3.10 shows the nullclines and trajectories for this example.
Figure 6.3.10. Fifth Linear System Example

Subsection 6.3.3 Second Order Systems

I used the coupled spring as a motivating example is a linear system. It is a second order system – in fact, it will be the only example I’ll consider of a second order system.
\begin{align*} m_1x_1^{\prime \prime} \amp = - k_1x_1 + k_2(x_2 - x_1)\\ m_2x_2^{\prime \prime} \amp = -k_2(x_2-x_1) \end{align*}
I’ll set the constants \(m_1 = m_2 =1\text{,}\) \(k_1=8\) and \(k_2=3\text{.}\) I’ll also set the initial conditions \(x_1(0) = x_1^\prime(0) = 0\) and \(x_2(0) = 1\) and \(x_2^\prime(0) = 0\text{.}\) These initial condition implies that the second spring (\(x_2\)) is pushed away from equilibrium. I don’t have a phase-plane diagram here, since this is a second order system. (Our phase-plane diagram intepretation in the previous section was specific to first-order systems.) However, I can solve using Laplace transforms anyway. I follow the standard procedure, taking transforms, solving the system by isolating and replacing, using partial fractions, adjusting the numerators, and taking the inverse transform.
\begin{align*} x_1^{\prime \prime} + 11 x_1 - 3x_2 \amp = 0\\ x_2^{\prime \prime} + 3 x_2 - 3x_1 \amp = 0\\ s^2 X_1 + 11 X_1 - 3X_2 \amp = 0\\ s^2 X_2 - s + 3X_2 - 3X_1 \amp = 0\\ X_2 \amp = \frac{(s^2+11) X_1}{3}\\ (s^2+3)X_2 - 3X_1 \amp = s\\ (s^2+3)\left( \frac{s^2+11}{3} \right) - 3X_1 \amp = s\\ \frac{s^4 + 14s^2+ 33 - 9}{3} X_1 \amp = s\\ \frac{s^4 + 14s^2 + 24}{3} X_1 \amp = s\\ X_1 \amp = \frac{3x}{s^4 + 14s^2 + 24} = \frac{3s}{(s^2+2)(s^2+12)}\\ X_2 \amp = \frac{s^2+11}{3} \frac{3s}{(s^2+2)(s^2+12)} = \frac{s^3 + 11s}{(s^2+1)(s^2+12)}\\ X_1 \amp = \frac{3s}{10(s^2+2)} - \frac{3s}{10(s^2+12)}\\ X_2 \amp = \frac{9s}{10(s^2+2)} + \frac{s}{10(s^2+12)}\\ x_1 \amp = \frac{3}{10} \cos \sqrt{2}t - \frac{3}{10} \cos \sqrt{12} t\\ x_2 \amp = \frac{9}{10} \cos \sqrt{2}t + \frac{1}{10} \cos \sqrt{12} t \end{align*}
This seems like a reasonable solution: the behaviour of each spring is the superposition to two sinusoidal waves with different periods. This won’t be a clear sine or cosinde way. It will be something that looks a little more erratic, but it will eventually repeat when both periods of both cosine functions have completed.
Here is an adjustment of the coupled spring, where each mass is attached to a fixed object. Then there are three springs in total: one attaching each mass to opposite walls, and one between them. I’ll write the system given by Newton’s laws of motion.
\begin{align*} m_2 x^{\prime \prime} \amp = -k_1 x + k_2 (y-x)\\ m_2 y^{\prime \prime} \amp = -k_3 y + k_2 (x-y) \end{align*}
I set the constants \(k_1 = k_3 = 2\text{,}\) \(k_2 = 1\text{,}\) and \(m_1 = m_2 = 1\text{.}\) For initial conditions, we set \(x(0) = y(0) = 0\) and \(x^\prime(0) = -1\text{,}\) \(y^\prime(0) = 1\text{.}\) These initial contidions show that the masses are pushed apart equal distances to start the system. I follow the standard steps of solution using Laplace transforms.
\begin{align*} x^{\prime \prime} + 3x - y \amp = 0\\ y^{\prime \prime} + 3y - x \amp = 0\\ s^2X + 1 + 3X - Y \amp = 0\\ s^2Y - 1 + 3Y - X \amp 0\\ Y \amp = \frac{1++X}{s^2+3}\\ (s^2+3) X - \left( \frac{1+X}{s^2+3} \right) \amp = - 1\\ \left( \frac{(s^2+3)(s^2+3) - 1}{s^2+3)} \right) X \amp = \frac{1}{s^2+3} - 1\\ (s^4+6s^2+8)X \amp = -s^2-2\\ X \amp = \frac{-s^2-2}{(s^2+4)(s^2+2)} = \frac{-1}{s^2+4}\\ Y \amp = \frac{1 + \frac{-1}{s^2+4}}{s^2+3}\\ \amp = \frac{s^2+4-1}{(s^2+4)(s^2+3)}\\ \amp = \frac{s^2+3}{(s^2+4)(s^2+3)} = \frac{1}{s^2+4}\\ x \amp = -\sin 2t\\ y \amp = \sin 2t \end{align*}
This is an interesting result. Having equal springs attached to either side of the system and an equal displacement away from the centre for both masses results in a single, clean sine way solution.

Subsection 6.3.4 General Theory via Eigenvalues

Having detoured briefly to some second order examples, let me return to first order constant coefficient linear system. I want to give a new understanding to the solutions of systems of two equations that I did before in the examples. The general linear system with two equations has the following form, to remind you.
\begin{align*} x^\prime \amp = ax + by \\ y^\prime \amp = cx + dy \end{align*}
I can use a 2 by 2 matrix with coefficients \(a,b,c,d\) to analyze the behaviour. Then I can make the functions \(x\) and \(y\) the coordinates of a vector and write the system in terms of this matrix.
\begin{equation*} \begin{pmatrix} x_1^\prime \\ x_2^\prime \end{pmatrix} = \begin{pmatrix} a \amp b \\ c \amp d \end{pmatrix} \begin{pmatrix} x_1 \\ x_2 \end{pmatrix} \end{equation*}
Let \(v\) be an eigenvector of the matrix and let \(\lambda\) be the corresponding eigenvectors.
\begin{equation*} \begin{pmatrix} x_1 \\ x_2 \end{pmatrix} = e^{\lambda t} v = \begin{pmatrix} e^{\lambda t} v_1 \\ e^{\lambda t} v_1 \end{pmatrix} \end{equation*}
To see why this is a solution, see what happens when the matrix acts on the vector.
\begin{align*} \begin{pmatrix} a \amp b \\ c \amp d \end{pmatrix} \begin{pmatrix} e^{\lambda t} v_1 \\ e^{\lambda t} v_2 \end{pmatrix} \amp = e^{\lambda t} \begin{pmatrix} a \amp b c \amp d \end{pmatrix} \begin{pmatrix} v_1 v_2 \end{pmatrix} \\ \amp = e^{\lambda t} \lambda \begin{pmatrix} v_1 v_2 \end{pmatrix} = \begin{pmatrix} \lambda e^{\lambda t} v_1 \lambda e^{\lambda t} v_2 \end{pmatrix} \\ \amp = \begin{pmatrix} \dfrac{d}{dt}e^{\lambda t} v_1 \dfrac{d}{dt} e^{\lambda t} v_2 \end{pmatrix} = \frac{d}{dt} \begin{pmatrix} e^{\lambda t} v_1 e^{\lambda t} v_2 ] \end{pmatrix} \end{align*}
If I allow for complex eigenvalues, the matrix has two eigenvalues, wth two linearly independent eigenvectors, giving two linearly independent solutions of this type. If the eigenvalues are real, there are exponential growth/decay solutions. If the eigenvalues are complex, these are sinusoidal solutions.

Subsection 6.3.5 Stability via Eigenvalues

Everything about a linear system can be determined by the eigenvalues of the associated matrix. For a linear system, the nullclines are both lines through the origin. Assuming they are not the same line (which would make the system redundant), the only steady state for a linear system in two equations is \((0,0)\text{.}\) As I’ve stated previously, there are six behaviours at the steady state for two-dimensional linear systems: stable and unstable foci, stable and unstable notes, centres and saddles. I can identify each case simply by the eigenvalues.
  • If both eigenvalues are real and negative, then \((0,0)\) is a stable node.
  • If both eigenvalues are real and positive, then \((0,0)\) is a unstable node.
  • If both eigenvalues are real, but one is positive and one is negative, then \((0,0)\) is a saddle point.
  • If both eigenvalues are complex with negative real part, then \((0,0)\) is a stable focus.
  • If both eigenvalues are complex with positive real part, then \((0,0)\) is an unstable focus.
  • If both eigenvalues are complex and purely imaginary, then \((0,0)\) is a centre.
The eigenvalues become the coefficients of the exponential solutions, which explains this list of behaviours. Only complex coefficients give sinusoidal behaviuors, as in the spiral foci and the circular centre. When there are real coefficients, the solutiosn only display growth and decay. The real part, in either case, is the growth or decay term. When the real part is negative, the solutions decay, which is stability. When the real part is positive, the solutions grow, which is instability.
Let \(M\) be the matrix and let Let \(\alpha = \text{ tr } M\) and \(\beta = \det M\text{.}\) Then the characteristic equation of the matrix can be written \(\lambda^2 - \alpha \lambda + \beta = 0\text{.}\) In addition, let \(\delta\) be the discriminant of the characteristic polynomial, \(\delta = \alpha^2 - 4\beta\text{.}\) Then I can redo the previous list.
  • If \(\beta > 0\text{,}\) \(\alpha \lt 0\) and \(\delta > 0\) then \((0,0)\) is a stable node.
  • If \(\beta > 0\text{,}\) \(\alpha > 0\) and \(\delta > 0\text{,}\) then \((0,0)\) is an unstable node.
  • If \(\beta \lt 0\text{,}\) then \((0,0)\) is a saddle point.
  • If \(\beta > 0\text{,}\) \(\alpha \lt 0\) and \(\delta \lt 0\text{,}\) then \((0,0)\) is a stable focus.
  • If \(\beta > 0\text{,}\) \(\alpha> 0\) and \(\delta \lt 0\) then \((0,0)\) is an unstable focus.
  • If \(\beta > 0\text{,}\) \(\alpha = 0\) and \(\delta \lt 0\) then \((0,0)\) is a centre.